Satisfaction Level of Cattle Breeders Through The Artificial Insemination Officers Services In Gorontalo District, Indonesia - Supardi; Mahludin Baruwadi (Technium Social Sciences Journal, 2024)
This study aimed to identify the characteristics of cattle breeders who receive Artificial Insemination (AI) services and analyze the level of satisfaction of acceptor breeders with the services of inseminator officers in Gorontalo Regency. The research method used is a survey method. The research sample was determined intentionally with the consideration that active breeders who adopt AI. Data were collected through direct observation in the field, interviews, and questionnaires using the Likert Scale. The research variables include five dimensions, such as: tangible, reliability, responsiveness, assurance, and attention. The data collected were processed using the Customer Satisfaction Index (CSI). The results showed that the majority of cattle breeders who became acceptors or 79.54% were in the age range of 31-60 years, 76.14% had secondary education and below, 82.96% had implemented AI between 3-9 years or an average of 6 years. The Weighted Total (WT) value of all attributes was 3.55 with a Customer Satisfaction Index (CSI) value of 71.03%. The CSI value is in the range of 66% - 80.99% which shows that the level of breeder satisfaction with AI services is in the satisfied category.